An analysis of leakage parameters of individual leaks on a pressure pipeline through the development and application of a standard procedure - Malde, Rahil (Department of Civil Engineering, 2015)
Water is a vital and scarce resource. Providing a sustainable and efficient means of transporting water is essential to the wellbeing of humankind. Most water distribution systems worldwide are ageing and deteriorating, as a result, leakage is a common problem. Modern water distribution systems use a variety of methods to minimise leakage, one of them is pressure management. However, the relationship between leakage and pressure is a complex one. The goals of this study were to develop a standard experimental procedure to determine the leakage parameters of a pipe with an individual leak, and to test a series of pipes using the newly developed procedure to determine their leakage parameters. There have been numerous experimental investigations into the leakage parameters; however, these investigations have variation in their methodologies. Therefore, developing a standard procedure will provide a consistent method for the accurate determination of the leakage parameters. Leakage parameters are important as they help to improve the understanding of the relationship between leakage and pressure. They are also important for use in the two main equations used to relate leakage and pressure, i.e. the N1 equation and the FAVAD equation. The determination of a variety of leakage parameters will help to determine whether both equations explain the behaviour of a variety of pipe samples, and which equation is better suited for use in leakage prediction.